The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/app10082639
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Modeling for Resilience Measurement: NATO Resilience Decision Support Model

Abstract: Despite its conceptual uncertainty, resilience is mostly about the measurement of capacity. Current studies confirm the importance of resilience measurement and the necessity to support policy makers with a measurement mechanism. A holistic approach considering the measurement of different resilience domains interactively and concurrently is the critical element in this endeavor. In parallel with the rise of popularity of resilience in international organizations, NATO has initiated a project with the objectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 19 publications
(29 reference statements)
0
10
0
1
Order By: Relevance
“…We have used the system dynamics modelling and simulation paradigm to develop both prototype and aggregated resilience models, as depicted in Figure 1 . The main rationale behind choosing this paradigm is to quantify NATO’s resilience-related capacities by a structure representing dynamic relations among vague resilience parameters over time in scenario-driven NATO operations and experiments [ 2 ]. The system dynamics modelling technique helps us understand and synthesize nonlinear behaviours of complex systems, such as resilience [ 25 , 26 ], by the help of simulation software analysing causal interrelations among the components that make up those systems [ 2 ].…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…We have used the system dynamics modelling and simulation paradigm to develop both prototype and aggregated resilience models, as depicted in Figure 1 . The main rationale behind choosing this paradigm is to quantify NATO’s resilience-related capacities by a structure representing dynamic relations among vague resilience parameters over time in scenario-driven NATO operations and experiments [ 2 ]. The system dynamics modelling technique helps us understand and synthesize nonlinear behaviours of complex systems, such as resilience [ 25 , 26 ], by the help of simulation software analysing causal interrelations among the components that make up those systems [ 2 ].…”
Section: Methodsmentioning
confidence: 99%
“…The main rationale behind choosing this paradigm is to quantify NATO’s resilience-related capacities by a structure representing dynamic relations among vague resilience parameters over time in scenario-driven NATO operations and experiments [ 2 ]. The system dynamics modelling technique helps us understand and synthesize nonlinear behaviours of complex systems, such as resilience [ 25 , 26 ], by the help of simulation software analysing causal interrelations among the components that make up those systems [ 2 ]. In accordance with the system dynamics methodology, we have conducted problem articulation and literature review on concept and measurement techniques of resilience concurrently, identified key resilience variables, made causality and behavioural analysis by building causal loop diagrams, modelled the dynamics of resilience via stock and flow diagrams, and developed user interfaces that consist of input and output dashboards for the prototype and aggregated resilience models.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations